Microelectronic circuits - Sedra, Adel S. (Holt, Rinehart, and Winston, 1987)
In the Third Edition of their bestselling design-oriented treatment of discrete and integrated circuits, Sedra & Smith anticipate future trends in the teaching of core electronics to electrical and computer engineering students. A major reorganization of the material enables students to get to the heart of the subject much more quickly. And for instructors, the text--now divided into three parts--is more flexible than ever before, allowing maximum latitude in course design. It includes over 800 end-of-chapter problems covering all topics with a graded level of difficulty. Covered are the latest circuit technologies of BiCMOS and Gallium-Arsenide (GaAs), data converters, and memory. Material on power-supply design, filters, and oscillators has been expanded.